Legal and Economic Feasibility of Circular Economy Practices in Small-Scale Food Enterprises: Case Study from Mushroom Snack Production in Indonesia - Satwhikawara, Rachmi; Natalita, Ferawati (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2025)
This study examines the legal and economic feasibility of small-scale mushroom crispy snack production as a circular economy strategy to reduce post-harvest losses in Indonesia. Using a case study approach, the research focuses on a mushroom-based micro, small, and medium enterprise (MSME) located in Cikarang, Bekasi Regency, which internally valorizes unsold or downgraded mushrooms into crispy snack products instead of discarding them as waste. The study applies an integrated analytical framework combining quantitative financial feasibility analysis using break-even point (BEP), return on investment (ROI), net present value (NPV), and payback period indicators with qualitative legal compliance assessment based on Indonesian food safety, licensing, and consumer protection regulations. The findings indicate that mushroom crispy production operates near its break-even point and does not yet function as an independent profit center. However, when evaluated within the enterprise’s integrated production system, the activity contributes positively by preventing economic losses from unsold fresh mushrooms, improving resource efficiency, and strengthening overall business resilience. From a legal perspective, the enterprise is feasible at its current scale, as it complies with core regulatory requirements, including possession of a valid home-industry food production license (PIRT) and adherence to basic food safety and labeling standards. Overall, the study demonstrates that mushroom snack production from surplus mushrooms is economically rational and legally compliant as a circular economy practice, even when short-term profitability remains limited. The findings highlight the importance of integrating financial analysis with legal compliance in assessing the sustainability of food-processing MSMEs.ABSTRAKStudi ini mengkaji kelayakan hukum dan ekonomi produksi camilan keripik jamur skala kecil sebagai strategi ekonomi sirkular untuk mengurangi kerugian pasca panen di Indonesia. Dengan pendekatan studi kasus, penelitian ini berfokus pada usaha mikro, kecil, dan menengah (UMKM) berbasis jamur yang berlokasi di Cikarang, Kabupaten Bekasi, yang secara internal mengolah jamur yang tidak terjual atau berkualitas rendah menjadi produk camilan keripik daripada membuangnya sebagai limbah. Studi ini menerapkan kerangka analitis terintegrasi yang menggabungkan analisis kelayakan finansial kuantitatif menggunakan titik impas (BEP), tingkat pengembalian investasi (ROI), nilai sekarang bersih (NPV), dan periode pengembalian modal dengan penilaian kepatuhan hukum kualitatif berdasarkan peraturan keamanan pangan, perizinan, dan perlindungan konsumen di Indonesia. Hasil penelitian menunjukkan bahwa produksi keripik jamur beroperasi dekat dengan titik impasnya dan belum berfungsi sebagai pusat keuntungan mandiri. Namun, ketika dievaluasi dalam sistem produksi terintegrasi perusahaan, aktivitas ini berkontribusi positif dengan mencegah kerugian ekonomi dari jamur segar yang tidak terjual, meningkatkan efisiensi sumber daya, dan memperkuat ketahanan bisnis secara keseluruhan. Dari perspektif hukum, perusahaan layak beroperasi pada skala saat ini, karena mematuhi persyaratan regulasi inti, termasuk kepemilikan lisensi produksi makanan industri rumahan (PIRT) yang valid dan kepatuhan terhadap standar keamanan pangan dan penandaan dasar. Secara keseluruhan, studi ini menunjukkan bahwa produksi camilan jamur dari jamur sisa merupakan praktik ekonomi sirkular yang secara ekonomi rasional dan sesuai dengan peraturan hukum, meskipun keuntungan jangka pendek masih terbatas. Temuan ini menyoroti pentingnya mengintegrasikan analisis keuangan dengan kepatuhan hukum dalam menilai keberlanjutan usaha mikro, kecil, dan menengah (UMKM) di sektor pengolahan makanan.